The Influence of User Trust and Experience On User Satisfaction Of E-Commerce Applications During Transactions in Mini Markets Using Delon and McLean Method - Dendy K. Pramudito; Ade Titin Sumarni; Enny Diah Astuti; Bunga Aditi; Magdalena (SEULANGA SYSTEM PUBLISHER, 2023)
In order to increase net advantages for users of e-commerce applications in minimarkets, this research attempts to quantify the degree and influence of experience and trust on user pleasure. This research employs a quantitative methodology. Direct observations of e-commerce applications, literature reviews, and the online distribution of Google Forms-assisted questionnaires to application users via social media were the methods used to collect data. Both statistical and demographic analysis were used to analyze the data for this study. Users of e-commerce applications make up the study's population. Purposive sampling was the method employed for sampling. With a total of 180 samples, the non-probability sampling approach makes use of the PLS-SEM theory. The majority of respondents expressed high levels of satisfaction with the e-commerce application in minimarkets, according to the data processing results. Because perceived utilitarian's path coefficient and t-test values are below the threshold, the analysis of the aspects of user experience represented by perceived hedonic and perceived utilitarian shows that perceived hedonic has a significant effect on user satisfaction while perceived utilitarian does not. The user happiness variable is significantly impacted by the trust variable. Perceived hedonic value, trust, and ease of use are factors that significantly impact customer satisfaction with e-commerce applications in minimarkets.